Anxiety and Depression in Healthcare Providers During Covid-19 Pandemic: A Cross-Sectional Study (British Journal of Multidisciplinary and Advanced Studies, 2023)
Since the COVID-19 pandemic, psychological well-being has soured considerably. Even elite intellectuals like physicians and researchers could not avert it. No convincing management, till now, have succeeded to unearth the requitals. Guesstimating the manifestations of anxiety and depression among medical professionals can unriddle the enormity of this burden. The objectives were to contrast scores of the Hamilton's anxiety (HAM-A) and depression (HAM-D) scales amongst covid-positives and covid-negatives, plus to estimate the relative risk of acquiring anxiety and depressive symptoms. We took clearance (928 dated 01.12.2021) from Institutional Ethics Committee SCB Medical College, Cuttack, before the study became operational. Nine hundred eighty-three healthcare workers’ HAM-A and HAM-D scores were slated for analysis. The participants were 35.95±11.54 years old on average. Of them, 613 (62.36%) were positive for covid. Pursuant to their HAM-A scores, 575 (58.49%) participants endured anxiety. It largely plagued nurses and pharmacists (245, 24.92%), followed by students (236, 24.01%) and clinicians (94, 9.56%). Depression afflicted 620 participants (63.07%). The greatest drivers were the students (301, 30.62%), followed by nurses, pharmacists (211, 21.46%), and the clinicians (108, 10.99%). Contrasted to the covid-negatives, the positive report-holders were less anxious (relative risk: 0.614; 95%CI: 0.538-0.701) and more depressive (relative risk: 2.541; 95%CI: 2.079-3.106). Similar results emerged from the subgroup analyses. When compared to covid positives, covid negatives endured more anxiety. On the contrary, covid-positive individuals manifested depression the most.